Effect of Current Ratio, Debt to Total Asset Ratio, Cash Turnover and Total Asset Turnover on Return on Assets in Food and Beverage Subsector Companies on the IDX 2015 - 2018 Period - Melvina; Handoko; Faathir Nurul Yaasiin (Jurnal Mantik, 2020)
This study aims to test whether Current Ratio, Debt to Total Asset Ratio, Cash Turnover and Total Asset Turnover have an influence on Return on Assets using the t test and F test. This research method uses a deductive approach, quantitative research types and descriptive research characteristics. . The population of the food and beverage sub-sector companies is 23 companies using purposive sampling, the sample size is 13 industries. The results showed that the partial current ratio has a positive and significant effect on ROA, by means of partial cash turnover has a negative and significant effect on ROA, but by means of partial DAR and TATO it has no effect on ROA. By simultaneous means Current Ratio, Debt to Total Asset Ratio, Cash Turnover and Total Asset Turnover have a significant effect on ROA. According to the exposure to the test results of the coefficient of determination observed through the Adjusted R Square value of 0.644, which means 64.4% of the variation in the dependent variable ROA that can be described by the variables (Current Ratio, Debt to Asset Ratio, Cash Turnover and Total Asset Turnover) where the rest value of 35.6% is influenced by other causes such as cash turnover variables, accounts receivable turnover, working capital.